Brans Group / Becxter Rym bin Amat… [et al.] - Amat, Becxter Rym; Noor, Ruzleh; Asli, Norsyahnaz; Jap, Nurul Afidah; Jalinin, Asmie (Faculty of Business Management, Universiti Teknologi MARA Sabah, 2013)
The name of our business is BRANS GROUP. We choose this name because it come from a combination of the names of each member of the group which we combine with our initials into the name "BRANS". a combination of the names of each member of the group which we combine with our initials into BRANS name. For example, Becxter "B", Ruzleh "R", Asmie "A", Nurul "N", Syahnaz "S". Ling Zhi Healthy Juice or Ling Zhi Antiquities health juice is fresh juices, energy and health. It is produced from a mixture of Ling Zhi, Pandan leaf, Roselle and honey. The juice is produced because we as consumers need to get good health while maintaining the energy and freshness of all time. The main characteristics in healthy Ling Zhi juice, no artificial colours containing materials, pure artificial flavours or preservatives. Some of the key features found in honey juice used in place of sugar. The main purpose is other than honey flavours consumers it also acts as a counterweight to stabilize sugar levels and nutrition and metabolism in the body. In addition, the material used is 100% of the natural world. Ling zhi juice is also suitable for all walks of life. The potential market for this product is very good as ling zhi juice products on the market yet. Furthermore, the enormous potential because it is based health products and competition for such products are not yet available. These businesses have a potential to being expanded. This is because the scope for healthy juice in Malaysia market nowadays, got a big potential for the healthy due to the growing awareness of health-conscious society in the routines of everyday life.